2017
DOI: 10.5194/amt-10-1519-2017
|View full text |Cite
|
Sign up to set email alerts
|

A new oxidation flow reactor for measuring secondary aerosol formation of rapidly changing emission sources

Abstract: Abstract. Oxidation flow reactors (OFRs) or environmental chambers can be used to estimate secondary aerosol formation potential of different emission sources. Emissions from anthropogenic sources, such as vehicles, often vary on short timescales. For example, to identify the vehicle driving conditions that lead to high potential secondary aerosol emissions, rapid oxidation of exhaust is needed. However, the residence times in environmental chambers and in most oxidation flow reactors are too long to study the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 43 publications
2
52
0
Order By: Relevance
“…It is known from model simulations and experimental studies that the O 3 oxidation of PAHs and organic molecules with C=C double bonds require an activation energy of 40 to 80 kJ mol −1 (Berkemeier et al, 2016;Lee et al, 2009;Pöschl et al, 2001;Stephens et al, 1989). Even though many different compounds can be found on soot surfaces, PAHs are considered to be a good reference compound (Slowik et al, 2004). A temperature change by 5 K would change the reaction speed and therefore t act by a factor of 2.…”
Section: Discussionmentioning
confidence: 99%
“…It is known from model simulations and experimental studies that the O 3 oxidation of PAHs and organic molecules with C=C double bonds require an activation energy of 40 to 80 kJ mol −1 (Berkemeier et al, 2016;Lee et al, 2009;Pöschl et al, 2001;Stephens et al, 1989). Even though many different compounds can be found on soot surfaces, PAHs are considered to be a good reference compound (Slowik et al, 2004). A temperature change by 5 K would change the reaction speed and therefore t act by a factor of 2.…”
Section: Discussionmentioning
confidence: 99%
“…In that stage, the oxidation products of precursors have condensed into the particle phase and formed secondary aerosol. However, because the oxidant concentrations are unrealistically high in PAM, the UV-light intensity used is non-tropospheric and the residence times are much shorter than in the atmosphere (e.g., Simonen et al, 2017), precursor oxidation products also have other possible fates; they can be oxidized too far and form non-condensable oxidation products before condensation (accelerated chemistry) and they can exit the reactor before the condensation occurs. Also, precursor oxidation products can be lost on the PAM walls although the losses on the walls are minimized by the chamber design (Lambe et al, 2011).…”
Section: Pam Artifacts and Lossesmentioning
confidence: 99%
“…The former study reported evidence for the incorporation of nitrogen into SOA. OFRs have also been increasingly employed to process emissions of vehicles, biomass burning, and other combustion sources (Table 1) in which NO can often be hundreds of ppm Martinsson et al, 2015;Karjalainen et al, 2016;Link et al, 2016;Schill et al, 2016;Alanen et al, 2017;Simonen et al, 2017). It can be expected that such a high NO input together with very high VOC concentrations would cause a substantial deviation from the good OFR operation conditions identified in Peng et al (2016).…”
Section: Introductionmentioning
confidence: 99%